A window on eternity : a biologist's walk through Gorongosa National Park - Wilson, Edward O. (Simon & Schuster, 2014)
"The remarkable story of how one of the most biologically diverse habitats in the world was destroyed, restored, and continues to evolve--with stunning, full-color photographs by two of the world's best wildlife photographers. In 1976, Gorongosa National Park was the premier park in Mozambique, boasting one of the densest wildlife populations in all of Africa. Across 1,500 square miles of lush green floodplains, thick palm forests, swampy lakes, and vast plains roamed creatures great and small, from herds of wildebeest and elephant to countless bird species and insects yet to be classified. Then came the civil war of 1978-1992, when much of the ecosystem was destroyed, reducing some large animal populations by 90 percent or more. Due to a remarkable conservation effort sponsored by an American entrepreneur, the park was restored in the 1990s and is now evolving back to its former state. This is the story of that incredible transformation and why such biological diversity is so important. In A Window on Eternity, world-renowned biologist and two-time Pulitzer Prize-winner Edward O. Wilson shows why biodiversity is vital to the future of the Earth, including our human population. It is in places like Gorongosa in Africa, explains Wilson, that our own species evolved. Wilson takes readers to the forested groves of the park's watershed on sacred Mount Gorongosa, then far away to deep gorges along the edge of the Rift Valley, places previously unexplored by biologists, with the aim of discovering new species and assessing their ancient origins. He treats readers to a war between termites and raider ants, describes 'conversations' with elephant herds, and explains the importance of a one-day 'bioblitz.' Praised as 'one of the finest scientists writing today' (Los Angeles Times), Wilson uses the story of Gorongosa to show the significance of biodiversity to humankind"--